WOUND-HEALING AND POTENTIAL ANTI-KELOIDAL PROPERTIES OF THE LATEX OF CALOTROPIS PROCERA (AITON) ASCLEPIADACEAE IN RABBITS. - Aderounmu, A O; Omonisi, A E; Akingbasote, J A; Makanjuola, M; Bejide, R A; Orafidiya, L O; Adelusola, K A (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Calotropis Procera (CP) has been used in the management of toothache, fresh skin burns, gum bleeding as well as others to make it qualify as a medicinal plant. This study was designed to assess its wound-healing property in rabbits and its potentials for anti keloidal activity.Fresh latex of Calotropis were obtained and evaluated phytochemically. Fifteen male rabbits were used and four excisional wounds were created on each rabbit. The rabbits were divided into five groups of three each. Group 1 was the negative control and received no treatment. The wounds of group 2 animals were treated with 2mL of Calotropis latex; group 3 with 2mL honey; and group 4 with a mixture of 1ml honey and 1 mL of the latex. The animals in group 5 were given 2mg triamcinolone intramuscularly. All the groups had their wounds treated daily for 21 days. The wounds’ diameters were measured on the day of wound creation, thereafter on days 7, 14 and 21 post wound creation. Biopsies of the wounds were taken on days 3 and 21 and viewed histologically. Phytochemical study of the latex revealed the presence of glycosides, tannins and alkaloids. The wounds were found to be significantly (p<0.05) reduced in groups treated with 50% latex in honey and triamcinolone, respectively, on day 7 post wound creation while there was a significant (p<0.05) reduction in wound surface area in all treated groups on days 14 and 21 post wound creation. Histological findings in untreated group showed thick bundle of collagen fibres some of which had broad based configurations, reminiscent of keloid. The group treated with 2mL of Calotropis latex revealed the presence of florid granulation tissues on day 3 while there was a marked reduction in quantity and size of collagen fibres on day 21 post wound creation which was comparable with what was seen for the triamcinolone-treated group.The general effect of Calotropis latex on wound-healing was noted. Likewise it’s similarity to that of triamcinolone, an anti-keloidal agent; this makes it a probable candidate for future anti-keloidal study using a suitable model.